Analysis Statistics in Practical Problems of Food Health - Cruz, Marcos Paulo Mesquita da; Cruz, Caroline Mesquita da; Filho, Ivan de Oliveira Holanda; Brilhante, Danilo Falcão Menezes; Brilhante, Davi Falcão Menezes (European Scientific Journal, ESJ, 2018)
This study aimed at the application of dietary supplementation in elderly people and, after a period, to prepare a statistical diagnosis of before and after some dimensional information to verify the great influence of diet in these patients. In order to do so, statistical analyzes were used, which are important tools that allow us to perceive the transformations in different chronological periods. As a result, it was possible to verify the history of the patients that were being altered in the last months by the new food supplement implanted, having a statistical explanation besides the nutritional one. However, care has been taken to demonstrate how misunderstanding can hamper interpretation and originate erroneous information from work.